Improvements in the Quality of Agricultural Soils Following Organic Material Additions Depend on Both the Quantity and Quality of the Materials Applied - Bhogal, Anne; Nicholson, Fiona A.; Rollett, Alison; Taylor, Matt; Litterick, Audrey; Whittingham, Mark J.; Williams, John R. (Frontiers in Sustainable Food Systems, 2018)
It is widely recognised that the application of organic materials is one of the most effective ways of increasing soil organic carbon (SOC) levels and improving soil quality, but do all forms of organic matter input have the same impact on soil properties? A network of seven experimental sites investigated the effects on soil quality of annual applications over a minimum of 3 years of compost and food-based digestate in comparison with farmyard manure (FYM) and livestock slurry. Two of the sites were existing experimental platforms which had previously benefitted from applications of FYM, livestock slurry and green compost allowing the effects of longer-term applications (6-17 years) on soil properties to be quantified. The application of all organic materials increased soil nutrient supply (total nitrogen, extractable phosphorus, potassium and magnesium) within a short timescale (<3 years), whereas SOC contents were only increased following the long-term (9 years or more) application of bulky organic materials (compost and FYM). SOC increases were associated with improvements in soil biological (microbial biomass) and physical properties (reduced bulk density), although the level of improvement was dependent on the quality of the organic material applied (as determined by its lignin content, an indicator of resistance to decomposition). Applications of low dry matter content materials (digestates and livestock slurries) had a limited capacity to improve soil biological and physical functioning, due to their low organic matter loading.